Single Voltage Differencing Gain Amplifier-Based Dual-Mode Quadrature Oscillator Using Only Grounded Passive Components - Channumsin, Orapin; Bhardwaj, Kapil; Srivastava, Mayank; Tangsrirat, Worapong; Petchmaneelumka, Wandee (My University, 2022)
This article describes the compact quadrature sinusoidal oscillator, which produces both voltage and current quadrature outputs at the same time. By utilizing a voltage differencing gain amplifier (VDGA) as an active element, the proposed dual-mode quadrature oscillator is realized with only three grounded passive elements, namely one resistor and two capacitors. The adjustment rules for the condition of oscillation and the frequency of oscillation are orthogonally controllable by the independent VDGA bias currents. Non-ideal influences on the circuit’s behavior are also examined in detail. PSPICE-based computer simulation was used to evaluate the theoretical hypotheses of circuit functioning.
Keywords: Dual-mode operation; Quadrature oscillator (QO); Tunable circuit; Voltage Differencing Gain Amplifier (VDGA)